Marine geology of Guam - Emery, K. O. (Kenneth Orris), 1914-1998 (Geology and hydrology of Guam, Mariana Islands., 1962)
"A study of the topography and sediments of submerged terraces, fringing reefs, channels, and the lagoon and of various shore features of a tropical island."